RF-Arbitrary Waveform Generation Based on Microwave Photonic Filtering - Rhys Adams; Reza Ashrafi; Junjia Wang; Mohammad Rezagholipour Dizaji; Lawrence R. Chen (IEEE Photonics Journal, 2014)
We demonstrate RF arbitrary waveform generation based on microwave photonic filtering. We use four-wave mixing in a silicon nanowire to increase the number of taps in an N-tap microwave photonic filter (MPF). Using a programmable optical filter, we can control the tap weights and, hence, the MPF response and corresponding generated waveform. We show uniform and apodized waveforms with four taps and seven taps with tunable central frequencies.